2020
DOI: 10.1177/2333794x20928215
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Residency Obesity and Overweight Training Curricula: A Systematic Review

Abstract: Background. Pediatric obesity has become a significant public health concern. Pediatricians are the ideal group to help identify and treat this epidemic, but unfortunately, many pediatricians are not trained to discuss obesity with patients and their families. Standardized training initiatives for pediatric residents on prevention and/or management of obesity are needed to equip emerging pediatricians to combat the obesity epidemic. Objectives. This systematic literature review aims to examine the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…24,25 This training is not currently universal within paediatric training, but is becoming more commonplace. 26 As such, it is not surprising that residents in our study, who receive training during their outpatient primary care rotations, were more likely to prescribe follow-up compared to the attending physicians. Continued standardization of residency curriculum is needed so that medical providers can learn to approach paediatric overweight and obesity management more systematically, as has been done with other chronic illnesses.…”
Section: Discussionmentioning
confidence: 72%
“…24,25 This training is not currently universal within paediatric training, but is becoming more commonplace. 26 As such, it is not surprising that residents in our study, who receive training during their outpatient primary care rotations, were more likely to prescribe follow-up compared to the attending physicians. Continued standardization of residency curriculum is needed so that medical providers can learn to approach paediatric overweight and obesity management more systematically, as has been done with other chronic illnesses.…”
Section: Discussionmentioning
confidence: 72%
“…Many HCPs perceived more problems in talking about weight and lifestyle in cases when parents had overweight or obesity, and/or when they expected the child and/or parent to react negatively. This relates to stigmatization of people with obesity that is present among both the general public and HCPs [20,21], and asks for education in communication strategies to address this sensitive topic [22], thereby improving HCPs' perceived self-efficacy and reducing barriers [2,14,15,23,24]. The majority of doctors (GPs, YHCPs and pediatricians) reported that insufficient time is a barrier to talking about weight and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, SE represents the drive to initiate and adapt behavior, aiming to match one's performance with the circumstances. Accordingly, an increased SE, which can result from training [14][15][16], could help HCPs overcome the barriers they perceive. However, how reported self-efficacy is associated with perceived barriers and the effort to start the conversation has not been studied, and insights into interdisciplinary differences are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many HCPs perceived more problems in talking about weight and lifestyle in cases when parents had overweight or obesity, and/or when they expected that the child and/or parent would react negatively. This relates to stigmatization of people with obesity that is present among the general public as well as among HCPs (20,21) and asks for education in communication strategies to address this sensitive topic (22), thereby improving HCP's perceived self-e cacy and reducing barriers (2,14,15,23,24). Furthermore, the majority of doctors (GPs, YHCPs and pediatricians) reported that insu cient time is a barrier to talk about weight and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of doctors (GPs, YHCPs and pediatricians) reported that insu cient time is a barrier to talk about weight and lifestyle. This is a commonly reported barrier in other studies as well, and asks also for health delivery system changes (2,14,15,23,24). Next to education, an improved and sustainable nancial and infrastructural framework is necessary to reduce the obesity stigma, improve obesity care for children, and positively impact HCP's perceived self-e cacy and barriers (6,9,20,21).…”
Section: Discussionmentioning
confidence: 99%